Konvergensi Sebagai Sarana Bertahan Media Massa: Case Study Tribun Sumsel - Harahap, Raegen; Hati, Putri Citra; Abdussalam, Kgs (Ampera: A Research Journal on Politics and Islamic Civilization, 2021)
Media convergence is a concrete step carried out by various mass media in the world as a result of technological transformation and internetization. The presence of the internet encourages the mass media to apply the concept of media convergence such as online media, e-papers, e-books, streaming radio and social media combined with other media. The purpose of this study was to determine how the implementation of the strategy used by the Sumsel Tribune in the era of media convergence, as well as the challenges faced and innovations made by the Sumsel Tribune in dealing with media convergence. The type of research used in this research is qualitative using the SWOT theory and media convergence theory. The research results reveal (1), the Sumsel Tribune is in the quadrant I position, is getting stronger and has a lot of potential opportunities by implementing an aggressive work strategy, (2) the media convergence system uses the concept of convergence dimensions according to Rich Gordon. Keywords: Newspapers, Media, Convergence, Tribune Sumsel Konvergensi media merupakan langkap konkrit yang dilakukan oleh berbagai media massa di dunia akibat dari transformasi teknologi dan internetisasi. Kehadiran internet mendorong media massa menerapkan konsep konvergensi media seperti media online, e-paper, e-books, radio streaming dan media sosial yang digabungkan dengan media lainnya. Adapun tujuan penelitian ini untuk mengetahui bagaimana penerapan strategi yang digunakan Tribun Sumsel di era konvergensi media, serta tantangan yang dihadapi, dan inovasi yang dilakukan Tribun Sumsel dalam menghadapi konvergensi media. Jenis penelitian yang digunakan dalam penelitian ini adalah kualitatif dengan menggunakan teori SWOT dan teori konvergensi media. Hasil penelitian mengungkapkan (1), Tribun Sumsel berada pada posisi kuadran I, semakin kuat dan memiliki posibilitas peluang yang banyak dengan menerapkan strategi kerja agresif, (2) sistem konvergensi media menggunakan konsep dimensi konvergensi menurut Rich Gordon. Kata Kunci: Surat Kabar, Media, Konvergensi, Tribun Sumsel